Improvement Of Writing Batik Skills Of Pkk Women, Tajinan Village, Kepanjen District, Malang Regency - Ratnawati Ratnawati; Kustyarini Kustyarini (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The purpose of this service at PKK RW.06 Tajinan village, Kepanjen sub-district, Malang Regency is to empower PKK members with various activities that can improve their economy. Activities carried out by making batik from the initial process until it becomes batik cloth and processing it into skills that have economic value. The method used is by transferring knowledge to members of PKK RW.06 Tajinan village, Kepanjen sub-district, Malang Regency, covering the process of batik until it becomes a skill that is ready to be sold. and food packaging with direct assistance. Results devotion to community train skills member of PKK RW.06 Tajinan village, Kepanjen sub-district, Malang Regency in the resulting batik PKK members.